Are Malaysian TVET graduates ready for the future? - Kenayathulla, Husaina Banu (Wiley, 2021)
Currently, we are at the beginning of the Fourth Industrial Revolution, where the rapid developments in genetics, artificial intelligence, robotics, nanotechnology, 3D printing and biotechnology are growing rapidly. It is expected that the majority of the children entering primary school today might end up working in jobs that do not yet exist. In such a fast-changing employment landscape, the ability to prepare for future skills will be required to take advantage of the opportunities presented by these trends. National Dual Training System has been implemented by the Ministry of Human Resource to ensure TVET graduates are equipped with the employability skills needed in the job market. Questionnaires were distributed to employers from different training institutions, industries and agencies. The employers were to evaluate the level of employability skills obtained by the graduates that had gone through the National Dual Training System and then, the employers were asked to identify employability skills needed to meet employment demands in the Fourth Industry Revolution. The findings provide insights to the policymakers and curriculum developers on the appropriate interventions that need to be taken to ensure our graduates are well equipped with the employability skills needed for the future.